Human and Nature Nexus - Chitrakar, Raju (Literary Studies, 2020)
‘Human being is the master of nature,’ is the long established axiom. This paper presents contrary argument from this. It claims that as human being is not master of nature, but one of its member species, and hence is subservient to it. The sooner humans understand this, and mould their conducts accordingly, the more they are likely to get peace, stability and development in the true worth. Hence, humans have to establish coping relationship with nature, not dominating one. To achieve the goal of establishing human and nature nexus, I first bring a case of the destruction of nature in Nepal and its side effects to the villagers. Then I present historical context of human and nature relationships. After that alternative ecocentric practices are presented. I draw conclusion from these.